TEKNIK-TEKNIK OBSERVASI (SEBUAH ALTERNATIF METODE PENGUMPULAN DATA KUALITATIF ILMU-ILMU SOSIAL) - Hasanah, Hasyim (At-Taqaddum, 2016)
The purpose of this paper to describe observation techniques, as an alternative method of collecting qualitative data for social sciences. Observation is one of the scientific activity is empirical, factual, and besed on the real text. Observations carried out through the experience derived from sensing without using any manipulation. The purpose of observation is the description, in qualitative research, observation produces theories and hypotheses, in quantitative research, observation used for testing theories and hypotheses. To be able to approach the social phenomenon, an observer needs to have close access to the settings and the subject. Doing the observation techniques have to heed the ethical principles such as respect for human dignity, respect for privacy and confidentiality, respect for justice and inclusiveness, balancing harms and benefits. Method of observation, if positioned as a part of the methodological spectrum (includes techniques and data collection strategies) in proportion, it will produce a high validity and reliability, as the fundamental basis for all methods, to find strategic development policies.